Performance of crossbred (Landrace x Desi) barrows reared with different floor space allowances in small fixed group size (Indian Journal of Animal Production and Management, 2017)
To review suitability of Indian Specifications (IS: 3916-1966) drafted way back for floor space requirement  of pigs, 36 crossbred (Landrace x Desi) barrows were reared with 3 different floor space allowances {n  = 4(group size) x 3(replications) = 12 each} including Indian Specifications as control group. Group TIS (control) had floor space allowance (0.9, 1.35 and 1.8 m2/pig during weaner, grower and finisher stage) as  per Indian Standards (IS: 3916-1966), while T2/3 and T1/2 treatment groups had 33% and 50% reduced floor  space allocation with fixed small (n=4) group size. Final body weight (28 week) was marginally higher in T2/3 group followed by T1/2 and TIS groups. Major performance traits i.e. body weight, average daily gain (ADG)  and feed conversion efficiency (FCE) did not differ significantly among the groups. For different treatment  groups, floor space coefficient (k value) was estimated based upon specified floor space allocation and  average body weight of pigs in respective group. Lowest value of coefficient of floor space allocation (k =  0.046) i.e. for T1/2 group was found higher than suggested critical k value (0.034) in most of the countries.  It was concluded that performance traits of crossbred barrows are not affected even at k value close to  0.05 in Indian climatic conditions.
Keywords: Crossbred barrow; Floor space; k value; Performance